Persistent expression of Cotesia plutellae bracovirus genes in parasitized host, Plutella xylostella. - Yonggyun Kim; Sunil Kumar (PLoS ONE)
Cotesia plutellae (= vestalis) bracovirus (CpBV) is symbiotic to an endoparasitoid wasp, C. plutellae, and plays crucial roles in parasitism against the diamondback moth, Plutella xylostella. CpBV virion genome consists of 35 circular DNAs encoding 157 putative open reading frames (ORFs). This study re-annotated 157 ORFs with update genome database and analyzed their gene expressions at early and late parasitic stages. Re-annotation has established 15 different viral gene families, to which 83 ORFs are assigned with remaining 74 hypothetical genes. Among 157 ORFs, 147 genes were expressed at early or late parasitic stages, among which 141 genes were expressed in both parasitic stages, indicating persistent nature of gene expression. Relative frequencies of different viral circles present in the ovarian lumen did not explain the expression variation of the viral ORFs. Furthermore, expression level of each viral gene was varied during parasitism along with host development. Highly up-regulated CpBV genes at early parasitic stage included BEN (BANP, E5R and NAC1), ELP (EP1-like protein), IkB (inhibitor kB), P494 (protein 494 kDa) family genes, while those at late stage were mostly hypothetical genes. Along with the viral gene expression, 362 host genes exhibited more than two fold changes in expression levels at early parasitic stage compared to nonparasitized host. At late stage, more number (1,858) of host genes was regulated. These results suggest that persistent expression of most CpBV genes may be necessary to regulate host physiological processes during C. plutellae parasitism.